(untitled) (Selecciones Matemáticas, 2023)
Conventional efficiency evaluation systems present little diversity in the type of variables considered. This aspect generally leads to errors in the application of the models and in the corresponding interpretation of results. This study proposes a dynamic model to measure the efficiency of decision-making units, based on non-parametric Multidirectional Efficiency Analysis (MEA). The model presented here considers a complete structure, which includes intertemporal variables (desirable/undesirable intermediate inputs and outputs), discretionary/non-discretionary inputs; desirable/undesirable inputs and outputs. Dynamic score is defined first in a particular version and then in a more general version, considering two optimization problems. The directional contribution of each variable is examined, showing excess inputs and deficit outputs. In addition, a dynamic inefficiency index to measure the number of times each input was used inefficiently, is presented for both desirable and undesirable cases.